Análise setorial das emissões de CO2 no Brasil - Morais, Alyson Fidelis de (2007)
In the last decades the world is showing clear signals that its absorption capacity of residues like industrial garbage, packages, plastics and paper is becoming exhausted. The nature responds by changing the climatic standards. Brazil, known by using clean energy sources, is becoming participant of the group of countries that most contribute for the increase of the greenhouse effect. The economic changes the country faced in the last decade have modified the Brazilian reality. Ahead of this it becomes necessary to study the causes of this increase in the world-wide pollution level and to characterize the current position of Brazil in this scene. In this work the objective is to verify, for Brazil, the main factors that had influenced the CO2 emissions proceeding from the fossil fuel burn by the economy intermediate sector form 1990 to 2003, highlighting the participation of the energy efficiency, the composition of the final demand and the productive structure of the country. For that, Structural Decomposition Analysis methodology was used. The main results show that although the country benefits from the efficiency using energy and specializes in less pollutant sectors, the growth of sectors as Transports, Agriculture, Metallurgy, Mining and Petroleum Products has contributed for an increase of the CO2 emissions during the period in analysis.